A blower for high temperature fumes in paper machine. (1st October 2019) - Kryłłowicz, Władysław; Szewczyk, Włodzimierz; Świniarski, Jacek; Pełczyński, Paweł
Highlights: The design of the blower allows to use it in micro-jet module in the paper machine. Control of the blower efficiency, fumes pressure and temperature was achieved. High pressure of the medium with a high temperature of up to 500 °C was obtained. Abstract: The article describes the project, strength calculations and construction optimization of a fan development, and its application in the blower, which was used for research of experimental, micro-jet blowing system, that regulates the moisture profile of the paper web. The blower was designed to compress to positive gauge pressure of 0.4 bar of fumes at a temperature of up to 500 °C with capacity of 1 m 3 /s. To meet these requirements, the blower was realized as an aggregate of four identical radial fans connected in series. Achieving the assumed pressure ratio for a single fan required the development of a specific rotor design and the use of steel with very good strength parameters at high operating temperatures. The fan was made in four copies and assembled into a prototype blower system for blowing fumes, which was successfully used in an experimental blower system for adjusting the cross profile of the web's moisture content in a paper machine.